Persepsi Pengunjung Tentang Daya Tarik Wisata Di Obyek Wisata Merapi Park - Wisnu Hadi; Fatikhah Rahmi Sholikhah (Journal of Tourism and Economic, 2025)
This study examines visitor perceptions of the tourist attractions at Merapi Park using a qualitative research method with a descriptive approach. The primary aim of the research is to identify and analyze visitor satisfaction regarding the available facilities and services. Survey results obtained through questionnaires, observations, and documentation indicate that the majority of visitors provide positive evaluations of accessibility, parking facilities, and staff service. Specifically, 48% of visitors rated the road conditions leading to Merapi Park as very good, while 68% stated that the staff service was friendly and polite. Public facilities such as restrooms and prayer rooms were also deemed adequate. In terms of pricing, entrance fees and food prices were considered affordable by respondents. These findings suggest a high level of visitor satisfaction, although there are areas for improvement. The results are expected to contribute to the development of national tourism and assist the management of Merapi Park in enhancing service quality.